Targeting parental motivation for change in childhood obesity: development and validation of the PURICA-S scale - Junne, Florian; Ehehalt, Stefan; Ziser, Katrin; Reinehr, Thomas; Wiegand, Susanna; Mander, Johannes; Martus, Peter; Mack, Isabelle; Oberle, Andreas; Wabitsch, Martin; Renner, Tobias; Zipfel, Stephan; et al. (International journal of obesity, 2019)
BACKGROUND: The high prevalence of overweight and obesity in childhood and adolescence call for effective and sustainable intervention strategies. Parental motivation for change may be a key factor in sustained behavioral improvement towards a healthy weight status of their offspring. In this study, we developed a new short instrument to assess parental motivation for change to facilitate motivation-tailored family interventions that promise improved effectiveness. - METHODS: The preexisting gold-standard instrument to assess motivational stages for change was adapted from the self to the parental perspective in a structured multistep Delphi procedure. The new instrument to assess parental motivation for change related to a health problem of their children was psychometrically evaluated in a sample (N = 193) of parents of children or adolescents with overweight or obesity. Confirmatory factor analysis, internal consistency, construct, and criteria validity were analyzed to test the psychometric properties of the new instrument. - RESULTS: As a result of the Delphi procedures, all 16 items were successfully transferred to the parental perspective. The hypothesized four-factor structure of the new instrument was approved, and internal consistency and criteria validity were good to very good (albeit with inconsistent findings for the subscale precontemplation). - DISCUSSION: In our investigated target group of parents with children with overweight or obesity, the new instrument to assess parental motivation for change proved to be a practicable, valid, and time-efficient short measure. The new instrument will enable more specific motivational stage-directed interventions that promise higher effectiveness of family-based interventions to fight childhood obesity. However, the subscale precontemplation seemed not fully suitable for the population investigated here and needs to be applied very carefully in future studies.
Gesehen am 05.12.2019